Evaluation of The 1499T>C Variant in The AKAP3 Gene of Infertile Men with Multiple Morphological Abnormalities of The Sperm Flagella Phenotype: A Case-Control Study - Elham Poursafari Talemi; Seyedeh-Hanieh Hosseini; Hamid Gourabi; Marjan Sabbaghian; Anahita Mohseni Meybodi (International Journal of Fertility and Sterility, 2024)
Background: Infertile men with multiple morphological abnormalities of the sperm flagella (MMAF) phenotypeexhibit mosaic sperm flagella abnormalities such as short, bent, coiled, and irregular flagella or absent flagella. Spermflagellum has an ultrastructurally axonemal structure that contains a large number of proteins. A-Kinase AnchoringProtein 3 (AKAP3) is expressed in spermatozoa. It may function as a regulator of motility and the acrosome reaction.This study aimed to compare genetic changes in infertile men suffering MMAF phenotype with the control group.Materials and Methods: In this case-control study, genetic variants of the AKAP3 gene were evaluated in 60 infertilemen with MMAF phenotype and 40 fertile men, as control. As exon five of the AKAP3 gene encodes the functionaldomain of this protein, its genetic variants were studied. Therefore, polymerase chain reaction (PCR)-sequencing wasundertaken on the DNA extracted from control and patients’ blood samples.Results: Sixty infertile men with MMAF phenotype and 40 normozoospermic men, as control, were enrolled inthis study. Four haplotype variants 1378T>C (rs10774251), 1391C>G (rs11063266), 1437T>C (rs11063265), and1573G>A (rs1990312) were detected in all patients and controls. On the other hand, a missense mutation 1499T>C(rs12366671) was observed in four patients with the homozygous form while seven patients carried the heterozygousform. No mutation was identified in the controls (P=0.04). The difference between the variation allele frequencies wasassessed in the patient and control groups by the Fisher Exact Test.Conclusion: In the homozygous form, this mutation changed Isoleucine to Threonine. This alternation occurred insidethe AKAP4 binding domain of the AKAP3 protein. The observed variants caused no significant deviation in thesecondary structure of AKAP3 protein and probably its function in spermatozoa flagella. So, these variants cannot beconsidered as the causes of MMAF phenotype in the studied patients.